Дослідження моделей і методів підвищення гнучкості розкладу IT -проєкту дистанційних послуг навчання - Кудрявцева, М. О. (ХНУРЕ, 2023)
This article discusses the necessity of researching models and methods for increasing schedule flexibility for IT project of services of distance learning. The requirements and restrictions for the algorithm of the flexible schedule are justified. Also, was described implementation of the existing IT project in which the algorithm will be integrated